2014
DOI: 10.1093/ije/dyt259
|View full text |Cite
|
Sign up to set email alerts
|

Is fluoride a risk factor for bone cancer? Small area analysis of osteosarcoma and Ewing sarcoma diagnosed among 0-49-year-olds in Great Britain, 1980-2005

Abstract: Background: Artificial fluoridation of drinking water to improve dental health has long been a topic of controversy. Opponents of this public health measure have cited the possibility of bone cancer induction. The study objective was to examine whether increased risk of primary bone cancer was associated with living in areas with higher concentrations of fluoride in drinking water.Methods: Case data on osteosarcoma and Ewing sarcoma, diagnosed at ages 0–49 years in Great Britain (GB) (defined here as England, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
20
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 32 publications
6
20
0
1
Order By: Relevance
“…The patterns of incidence of ES across countries concur with the published literature [2] with rates somewhat higher among males than females up to the early peak in female incidence (at ages [10][11][12][13][14] which occurs 5 years earlier on average than in men; women have higher rates at ages 15-24. Although the cause of ES remains unknown, some clues regarding its etiology have emerged from the few case-control studies reported. Parental exposure to environmental factors [6,[11][12][13] leading to the disruption of normal embryological development of tissues by hormonal, environmental, or genetic factors during pregnancy has been implicated in its etiology [15].…”
Section: Discussionsupporting
confidence: 84%
“…The patterns of incidence of ES across countries concur with the published literature [2] with rates somewhat higher among males than females up to the early peak in female incidence (at ages [10][11][12][13][14] which occurs 5 years earlier on average than in men; women have higher rates at ages 15-24. Although the cause of ES remains unknown, some clues regarding its etiology have emerged from the few case-control studies reported. Parental exposure to environmental factors [6,[11][12][13] leading to the disruption of normal embryological development of tissues by hormonal, environmental, or genetic factors during pregnancy has been implicated in its etiology [15].…”
Section: Discussionsupporting
confidence: 84%
“…A recent UK ward‐level ecological study using a broadly similar method to this study found no association between measured fluoride levels in drinking water and osteosarcoma .…”
Section: Discussionsupporting
confidence: 48%
“…Blakey et al [164] 2014 Ecological analysis using high-quality population-based data on osteosarcoma and Ewing sarcoma cases diagnosed in Great Britain between 1980 and 2005. Fluoride levels were assigned on a small-area basis, allowing improved classification of exposure.…”
Section: Discussionmentioning
confidence: 99%
“…The analysis, which is more informative than those of previous ecological studies, found no correlation between fluoridated water consumption and these cancers. [164] • A recent Water Fluoridation Health Monitoring report published by Public Health England [95] found no evidence of a positive association between fluoridation and osteosarcoma or other forms of cancer.…”
Section: Osteosarcomamentioning
confidence: 99%